2021
DOI: 10.1002/pca.3051
|View full text |Cite
|
Sign up to set email alerts
|

Using 13C‐NMR dereplication to aid in the identification of xanthones present in the stem bark extract of Calophyllum brasiliense

Abstract: Introduction: Xanthones are metabolites with a variety of biological properties. The Clusiaceae family, which until recently included the genus Calophyllum, is recognised for its production of monohydroxylated and polyhydroxylated xanthones. Presently, C. brasiliense is the only Calophyllum spp. known to occur in the Yucatan peninsula. Objective: To use a combination of traditional phytochemical methods and carbon-13 nuclear magnetic resonance ( 13 C-NMR) dereplication analysis to identify xanthones in the ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 61 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Thus, the aim of this study was to characterize major compounds from propolis samples collected in various phytogeographical zones of Benin and Congo (Africa) using 13 C nuclear magnetic resonance (NMR) dereplication with MixONat software 43,44 . A preliminary study using a database (DB) containing NPs previously reported from propolis together with their 13 C predicted chemical shifts ( δ C ) did not yield any usable data compared to the satisfactory results usually obtained with plant extracts 43–45 . This can be explained by the chemical composition of propolis, which is highly dependent on the local flora, making it impossible to construct a chemotaxonomic DB.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, the aim of this study was to characterize major compounds from propolis samples collected in various phytogeographical zones of Benin and Congo (Africa) using 13 C nuclear magnetic resonance (NMR) dereplication with MixONat software 43,44 . A preliminary study using a database (DB) containing NPs previously reported from propolis together with their 13 C predicted chemical shifts ( δ C ) did not yield any usable data compared to the satisfactory results usually obtained with plant extracts 43–45 . This can be explained by the chemical composition of propolis, which is highly dependent on the local flora, making it impossible to construct a chemotaxonomic DB.…”
Section: Introductionmentioning
confidence: 92%
“…43,44 A preliminary study using a database (DB) containing NPs previously reported from propolis together with their 13 C predicted chemical shifts (δ C ) did not yield any usable data compared to the satisfactory results usually obtained with plant extracts. [43][44][45] This can be explained by the chemical composition of propolis, which is highly dependent on the local flora, making it impossible to construct a chemotaxonomic DB. Thus, to decipher major compounds from Beninese and Congolese propolis, in the present work we performed high-performance liquid chromatography coupled with ultraviolet and evaporative light scattering detection mass spectrometry (HPLC-UV-ELSD-MS) and gas chromatography coupled with mass spectrometry (GC-MS) analyses on crude propolis extracts to identify their main structural features and build corresponding DBs of NPs suitable for MixONat software.…”
mentioning
confidence: 99%
“…In addition, as a complementary approach to MS within a chemometric model, MixONat was successfully used for confirming the structures of high anti-advanced glycation end-products (AGEs) activity markers directly from crude bark extracts of Garcinia parvifolia prior to their isolation [50] . Other relevant literature has also reported the use of MixONat for elucidating the composition of propolis samples [51][52] , xanthones from Calophyllum brasiliense [53] , and polyphenolic FCs from Clusia flava Jacq. [54] .…”
Section: Dereplication Strategies Based On 13 C Nmr Spectra Datamentioning
confidence: 99%
“…160 Recently, using 13 C-NMR, a dereplication soware (MixONat) 124 was developed that allowed the distinction of structurally close NPs, including stereoisomers, and aided the identication of xanthones in Calophyllum brasiliense. 124,161 In another study that used 1 H-NMR, Grienke et al developed a workow ELINA (Eliciting Nature's Activities) based on a heterocovariance analysis, which can detect chemical features that correlate with bioactivity before isolation; using this approach, the authors discovered lanostane triterpenes from the extract of the fungus Fomitopsis pinicola. 125 2.5.…”
Section: Reviewmentioning
confidence: 99%